When the sun danced : myth, miracles, and modernity in early twentieth-century Portugal - Bennett, Jeffrey S. (Studies in religion and culture (Charlottesville, Va.), 2012)
Between May and October of 1917, three young shepherds were reportedly visited six times by an apparition of the Virgin Mary near the town of Fátima in Portugal. At the final apparition event, approximately 70,000 visitors gathered to witness a prophesied miracle intended to convince the public that the children's visions were of divine origin. The miracle took the form of a solar anomaly; witnesses claimed that the sun began to "dance." Exploring the early development of the cult of the Virgin of Fátima and the overthrow of the liberal, secular government by pro-Catholic elements, Jeffrey Bennett offers the first book-length scholarly study of the cult's relationship to the rise of authoritarian politics in Portugal. When the Sun Danced offers a fascinating look at the cultural dynamics that informed one of the most turbulent periods in the nation's history--Publisher.